'A New Way to Live My Life': How Al-Anon Influences Resilience: A Qualitative Account. Issue 1 (2nd January 2016) - Corrigan, Brid
ABSTRACT: Alcoholism can have deep and enduring negative outcomes for the close relatives of problem drinkers. This qualitative study explored Al-Anon's (a 12-step mutual-help group for relatives) role in enhancing resilience among its members. Data from 2 focus groups ( n = 5 and n = 3, respectively) and 2 individual interviews were analyzed using interpretative phenomenological analysis. Participants described increased positive adaptation in terms of personal growth and enhanced functioning. The findings indicated that Al-Anon plays a role in fostering resilience among members by providing protective factors. The implications were discussed in the context of bolstering clinical interventions.